Perioperative metformin use in patients undergoing total joint replacement surgery: protocol for a randomised, placebo-controlled pilot study - Aidan Morrell; Steven Shelofsky; Hannah Hoffman; Cole McCallister; Thomas W Huff; Kathryn L Schabel; Avital Y O’Glasser; Ryland P Kagan (BMJ Open)
Introduction Patients with poor perioperative glycaemic control after total joint arthroplasty are at an increased risk of complications, mortality, delayed return to function and increased costs of care. Although correction of hyperglycaemia has been shown to improve patient outcomes, there is a lack of consensus regarding optimal perioperative glucose management after total joint replacement surgery. This pilot study aims to assess the feasibility of performing a multicentre randomised controlled trial to investigate the effect of perioperative metformin use on glycaemic control in the setting of total joint arthroplasty.Methods and analysis This blinded, placebo-controlled, pilot randomised controlled trial will enrol 40 participants aged 18–99 years undergoing total hip or knee arthroplasty at a single academic tertiary centre. Patients will be randomly allocated to two groups of 20 participants each and will receive metformin or a placebo, respectively, for 2 weeks preoperatively, continued on the day of surgery, and up to 2 days postoperatively. The primary outcome is a composite of four endpoints to assess study feasibility: timely recruitment, timely study drug administration, protocol adherence and retention. Secondary outcomes include perioperative glycaemic variability, sliding scale insulin utilisation, hospital length of stay and 90-day rates of infection, mortality and readmission. Analyses will be on an intention-to-treat basis.Ethics and dissemination The protocol was approved by Oregon Health & Science University Institutional Review Board, STUDY00025798. Written informed consent will be obtained for study participation. Findings will be disseminated via publication in peer-reviewed journals and conference presentations.Trial registration number NCT06280274.